A new species of Ceratosticha Meyrick, 1935 (Lepidoptera: Psychidae) from Korea - Roh, Seung Jin; Shin, Young-Min; Byun, Bong-Kyu (Zootaxa, 2019)
Ceratosticha lineata Roh & Byun, sp. n., is described from Korea. Adults, genitalia, and larvae of the species are described, and DNA barcodes are provided.